The Role of Job Satisfaction Intervening Mediation: Servant Leadership, Organizational Culture and Organizational Citizenship Behavior (OCB) (Case Study on Employees of PT. Bank Sumut Medan Head Office) - Farisi, Salman; Prayogi, Muhammad Andi (Journal of International Conference Proceedings, 2023)
The purpose of this study was to determine the effect of servant leadership and organizational culture on organizational citizenship behavior (OCB) through job satisfaction as an intervening variable. In this study, the research method used was a quantitative research method and the type of research used in this study was associative research. The place of research is the object of a study. This research will be carried out at PT. Bank SUMUT Medan head office on jl. Imam Bonjol No. 18 Medan. The population of this study is the employees of PT. Bank SUMUT Medan Head Office consists of 17 divisions, namely 471 people. The sample used in this study was the slovin sample, with 81 samples taken. The data analysis technique used in this study is SEM-PLS analysis, as for the results of this study, there is an influence of Servant Leadership on Organizational Citizenship Behavior at PT. Bank Sumut Branch Medan Medan. There is an influence of Organizational Culture on Organizational Citizenship Behavior at PT. Bank Sumut Branch of Medan There is an influence of job satisfaction on Organizational Citizenship Behavior employee work at PT. Bank Sumut Branch of Medan. Organizational Citizenship Behavior. In this study Servant Leadership influences Organizational Citizenship Behavior which is mediated by satisfaction at PT. Bank Sumut Branch of Medan Medan in this study Organizational Culture influences Organizational Citizenship Behavior mediated by satisfaction with PT. Bank Sumut Branch Medan.